Relationship between bronchial reversibility and tracheobronchial clearance in patients with chronic bronchitis. Issue 2 (February 1997) - Moretti, M; Lopez-Vidriero, M T; Pavia, D; Clarke, S W
Abstract : BACKGROUND: Patients with chronic bronchitis show a large intersubject variation in sputum rheology, tracheobronchial clearance, and reversibility of airflow obstruction to beta 2 agonists. The bronchial mediators which are known to cause bronchoconstriction, mucosal oedema, mucus hypersecretion, and cough can also affect mucociliary transport. The aim of this study was to ascertain whether changes in tracheobronchial clearance and sputum rheological properties in patients with chronic bronchitis were associated with a specific degree of airflow reversibility assessed as the bronchial response to an inhaled beta 2 agonist (fenoterol 400 micrograms). METHODS: Bronchial reversibility (percentage change in baseline forced expiratory volume in one second (FEV1)) was measured in 26 patients with chronic bronchitis on three separate occasions, at least one week apart. Tracheobronchial clearance was evaluated by a non-invasive radioaerosol technique, and an oscillatory viscometer was used for measuring sputum apparent viscosity and elasticity. The number of coughs (productive and nonproductive coughs), the wet weight of sputum, and its radioaerosol content were recorded during the six hour clearance period, as well as the 24 hour sputum production. RESULTS: The change in FEV1 after fenoterol was less than 15% in 12 patients and more than 15% in 14. Patients with airways reversibility of more than 15% had faster tracheobronchial clearance, more coughs, lower sputum viscosity and elasticity, and larger 24 hour sputum production than those with airways reversibility of less than 15%. CONCLUSIONS: In patients with chronic bronchitis a large bronchodilator response is associated with faster clearance of mucus by mucociliary transport and coughing.